ASSESSMENT OF ORAL HYGIENE AMONG THE SOVIET CHINCHILLA AND NEWZEALAND WHITE RABBIT – A CROSS-SECTIONAL SURVEY - Gousalya V; Prabu D; Rajmohan M; Bharathwaj VV; Dinesh Dhamodhar; Elakiya S (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
Dental problems in rabbits are distinctive due to their dental anatomy and physiology. This cross-sectional study aims to assess the oral hygiene among the Soviet chinchilla and Newzealand white rabbit. The breeds taken were the soviet chinchilla and Newzealand white rabbit, and they were classified based on their age, such as 0-3 yrs, 4-6 yrs, 7-9 yrs and 10-12 yrs and gender as reported by the owner. Malocclusion, gingivitis, calculus, mobility, and osteodystrophic dental disorder were recorded. A chi-square test was performed to find the association between oral health status and breed. Prevalence of osteodystrophic disorder among the rabbit breed were grade 1 (6.3%), grade 2 (47.7%), grade 3 (37.5%), grace 4 (3.9%), grade 5(4.6%). Prevalence of malocclusion among the breeds were stage 1 (53.1%), stage 2 (24.2%), stage 3 (22.7%). Prevalence of mobility among the rabbit M-0 (37.5%), M-1 (37.5%), M-2 (18.0%), M-3 (7.0%). Association between the breeds and osteodystrophic diseases were statistically significant (p < 0.05). Association between the breeds and malocclusion, calculus and mobility were not statistically significant. There is a statistically significant (p<0.05) association between the breeds and the mild form of gingivitis. This study concludes that there is a significant difference only in osteodystrophic dental diseases and gingivitis between the breeds. Furthermore, malocclusion, tooth mobility and calculus have no statistically significant difference between the breeds. However, the prevalence of oral diseases in rabbits is more common, which can be prevented by a healthy fibre-rich diet and regular dental checkups.